«Հայաստա՛ն, իմ սեր»-ը՝ որպես խոստովանություն և դաս - Դոլուխանյան, Աելիտա (Զանգակ հրատ.)
Замысел сборника «Армения, любовь моя» весьма актуалeн, продуман, поучителeн, трогателeн и заразителен. Было бы желательно, чтобы студенты разных факультетов главного педагогического вуза республики получили от этой книги урок патриотизма. Это был бы правильный и важный урок, направленный на сохранение армянства и укрепление национального духа. Автор сборника «Армения, любовь моя» - человек, преданный Родине, историк, хорошо осведомленный о нашей национальной судьбе. Эта книга доказывает, насколько важно семейное воспитание. Начиная с колыбели, с материнским молоком ребенок должен впитать любовь к Родине. Произведение «Армения, любовь моя» и одноименный сборник проникнуты глубоким оптимизмом, мыслями о будущем Родины. Книга является правильным и полезным уроком патриотизма, особенно для подрастающего поколения. We are especially interested in the miscellany “Armenia, my Love” the meaning of which is topical, well thought, instructive, moving and contagious. It would be most desirable if the students of different faculties of the mother Pedagogical University should get a lesson of patriotism from this book. That would be a true and significant lesson aimed to preserve Armenian people and reinforce their national spirit. The author of the miscellany “Armenia, my Love” is a man devoted to his homeland, a chronicler well aware of our national fate. This book explains very clearly how important is family education. From the cradle and with his mother’s milk a child should suck the love of his homeland. The work “Armenia, my Love” and the miscellany of the same title are full of profound optimism toward the future of our homeland. The book is an accurate and useful lesson of patriotism, especially for the forthcoming generation.
Keywords: Դասավանդման և դաստիարակության մեթոդիկա